2010
DOI: 10.1016/j.stem.2010.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Origin of New Glial Cells in Intact and Injured Adult Spinal Cord

Abstract: Several distinct cell types in the adult central nervous system have been suggested to act as stem or progenitor cells generating new cells under physiological or pathological conditions. We have assessed the origin of new cells in the adult mouse spinal cord by genetic fate mapping. Oligodendrocyte progenitors self-renew, give rise to new mature oligodendrocytes, and constitute the dominating proliferating cell population in the intact adult spinal cord. In contrast, astrocytes and ependymal cells, which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

38
683
5
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 549 publications
(731 citation statements)
references
References 56 publications
38
683
5
5
Order By: Relevance
“…12 Dividing cells express markers of mature astrocytes or oligodendrocytes, but remain in situ rather than migrating to the surrounding tissue. 13 After spinal cord injury in the rat, NPCs proliferate and differentiate into glial cells but not neurons, 5,14,15 and can migrate toward an injury site. 11,14,16 Endogenous NPC present in the adult human spinal cord have been isolated from fresh autopsy tissue, cultured, and shown to differentiate into neurons and glial cells in vitro.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Dividing cells express markers of mature astrocytes or oligodendrocytes, but remain in situ rather than migrating to the surrounding tissue. 13 After spinal cord injury in the rat, NPCs proliferate and differentiate into glial cells but not neurons, 5,14,15 and can migrate toward an injury site. 11,14,16 Endogenous NPC present in the adult human spinal cord have been isolated from fresh autopsy tissue, cultured, and shown to differentiate into neurons and glial cells in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…13 After spinal cord injury in the rat, NPCs proliferate and differentiate into glial cells but not neurons, 5,14,15 and can migrate toward an injury site. 11,14,16 Endogenous NPC present in the adult human spinal cord have been isolated from fresh autopsy tissue, cultured, and shown to differentiate into neurons and glial cells in vitro. 17,18 One of the common markers for progenitor cells, nestin, is increased in the ependyma of human spinal cords from patients with multiple sclerosis, 19 amyotrophic lateral sclerosis (ALS), and spinal tumors, 20 and in hydrocephalic infants.…”
Section: Introductionmentioning
confidence: 99%
“…Following spinal cord injury (SCI), a cascade of pathological processes occurs, including the breaking down of the vasculature system, edema, infiltration of immune cells, inflammation, initiation of wound healing processes, seizing of ongoing neurotransmission, gliosis/glial scar formation, cell death, demyelination, and remyelination (7), along with activation of neural stem/ progenitor cells (NPCs) attempting to participate in neural repair (8). Often, prolonged activation of immune cells, including microglia, lymphocytes, and macrophages, leads to secondary lesions of the nervous system, creating a very harsh environment for already compromised CNS neurons to regenerate axons (9).…”
mentioning
confidence: 99%
“…It has been widely accepted that neural stem cells (NSCs) reside in many regions of the adult CNS (8,12,13). CNS injury frequently causes neuronal loss.…”
mentioning
confidence: 99%
“…Recent work by Sellers et al [68] demonstrated differential cell fate of NG2 cells after SCI; NG2 cells generated 24 h after injury gave rise to astrocytes, whereas those generated 1 week postinjury produced OLs. However, more recent data using lineage tracing following SCI call the ability of OPCs to give rise to astrocytes after SCI into question [69]. Direct evidence that NG2 cells contribute to replacement of mature OLs after SCI was recently provided using the CNP-EGFP (2',3'-Cyclic-nucleotide 3'-phosphodiesterase gene-enhanced green fluorescent protein) mouse to definitively show that EGFP + NG2 + cells differentiate into OLs after SCI [70].…”
Section: Replacement Of Ols By Endogenous Progenitors After Scimentioning
confidence: 99%